Six Sigma(6σ) quality system: Management - García P., Manuel (2001)
The present article presents a system of quelity where the statistic and teh administration creates a new form of making quality with the data to arrive at the level Six Sigma (6σ) the means 3.4 defects for million of opportunities (DMPO) and it is based on identifying the opportunities of defects in the company, suppliers and clients.